Dinamika Pondok Pesantren di Kabupaten Padang Lawas: Suatu Kajian Historis-Sosiologis terhadap Elemen Pokok Pesantren - Fauzan Tsani Al Hakimi (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas Gunung Tua, 2025)
This study examines the dynamics of the main elements of pesantren (Islamic boarding schools), including kiai (Islamic scholars), santri (students), pondok (dormitories), mosques, classical Islamic texts, and institutional development in Padang Lawas Regency. A qualitative method with historical and sociological approaches was employed. Data were collected through interviews, observations, and document analysis and analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing and verification. The findings indicate that pesantren have undergone significant transformation. The role of the kiai has shifted toward more modern leadership, supported by stronger inter-pesantren networks. The number of santri has steadily increased, while many alumni have become teachers, Islamic preachers (da'i), and founders of new pesantren. Student dormitories and mosques have developed into permanent facilities, with mosques serving as centers for learning as well as worship. The use of classical Islamic texts has changed due to the declining availability of qualified instructors. Furthermore, pesantren institutional development evolved from majelis taklim and madrasah ibtidaiyah into comprehensive Islamic educational institutions. These findings demonstrate the adaptability of pesantren to social, educational, and institutional changes while preserving their fundamental identity.